Redovisning i komplexa situationer : Hur tolkningar och bedömningar görs för att ge en rättvisande bild - Poromaa, Cassandra; Savela, Marie (2014)
In most countries accounting is regulated in one way or another. There is nothing showing the manner in which one is most suitable when it comes to present a true and fair view to business stakeholders. If a situation is complex, which is characterized by difficulties to get an overall picture of the situation and uncertainty when the situation is difficult to handle and guidelines, recommendations and practices are missing the true and fair view becomes difficult to convey. The transformation of Kiruna is a complex situation primarily because there never has been handled a similar situation in Sweden before but also because the situation, among other things, is affecting many different areas. A case study which aims to describe and analyze the challenges in municipal accounting in complex situations was conducted. This was done using three semi-structured interviews involving different perspectives. Two research questions were answered to define the purpose of the study regarding the challenges associated with the situation and how the municipal accounting is interpreted and reviewed in order to convey a true and fair view in a complex situation. The different perspectives were set against each other and against previous researches regarding the subject and it revealed differences in both the challenges and how the municipal accounting is interpreted and reviewed in current situation. The result shows that the municipality of Kiruna experiencing challenges regarding the presentation of a true and fair view to its stakeholders in a way they comprehend. In order to face the challenges the municipality consider necessary to depart from recommendations as they not think of them as applicable in the complex situation. The conclusion of the study is that the municipality of Kiruna and Rådet för kommunal redovisning’s perspectives differs regarding how to convey a true and fair view in a complex accounting situation that the city transformation of Kiruna causes. The municipality of Kiruna consider the main challenge ...